Electrical, optical and photoconductive properties of Sn-doped indium sulfofluoride thin films - Vygranenko, Yuri (2021)
This work reports on undoped and Sn-doped indium sulfofluoride thin-films deposited by radio-frequency plasma-enhanced reactive thermal evaporation. The deposition was performed evaporating pure indium or indium-tin alloy in SF6 plasma at substrate temperatures ranging from 373 to 423 K. Rutherford backscattering analysis and secondary-ion mass spectrometry were used to determine the chemical composition of the films. The film characterization includes electrical, optical, and photoconductivity measurements. The resistivity of undoped material varies in a wide range of 1 G Omega-cm to 2 T Omega-cm depending on deposition conditions. Sn doping leads to a decrease in the resistance down to 8 M Omega-cm. The films are highly transparent in the visible-infrared region due to an indirect bandgap of 2.7-3 eV. Moreover, the doped material is highly photosensitive in the blue -UV region. Photoconductivity kinetics under various excitation conditions was also studied. The synthesized material is a promising candidate for a buffer layer in chalcogenide-based solar cells.